Simulation and Analysis of Bottom-contact Pentacene-based OTFTs Devices - Elgeme, Najeb; khershif, Radwan; Rehan, Salahadeen; Elmrabet, Abdraof (AlQalam Journal of Medical and Applied Sciences, 2026)
This study uses COMSOL Multiphysics to simulate and analyze bottom-contact pentacene-based Metal-Insulator-Semiconductor (MIS) devices. Organic semiconductors like pentacene are promising for low-cost, flexible electronics due to their high field-effect mobility and compatibility with solution-based processing. The two-dimensional 2D simulation framework investigates electrostatic potential distribution, hole concentration profiles, current-voltage (I–V) characteristics, and capacitance-voltage (C–V) behavior in MIS structures with a gold gate electrode, PMMA dielectric layer, and pentacene active layer. The model captures drift-diffusion transport and electrostatic interactions across interfaces. Morphology-driven effects are introduced through synthetic grain models based on AFM data. The results show the role of contact geometry and surface morphology on charge carrier accumulation and electrical performance. The study demonstrates the predictive capability of Multiphysics simulation in optimizing organic transistor design and provides a scalable framework for evaluating new materials, dielectric configurations, and structural layouts in organic electronics.